Penggunaan monopoli Hijaiyah untuk meningkatkan pengetahuan huruf-huruf Hijaiyah pada siswa dengan hambatan pendengaran - Silvi Sundari (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2020)
The research aims to improve knowledge of the letters hijaiyah to their students with hearing impairment using Monopoly Hijaiyah. The research is experimental research with a pre-Experimental design using one group pretest-posttest done in 2 boys and 1 female student with hearing impairment in VII class in SKh Al-Kautsar Cilegon city. The technique of the data is observation, test, and documentation. Learning media covered instruments physically used to convey the contents of the material both in audio and visual learning. For students with hearing impairment in the time learning process, they would optimize their sense of vision, so the media had to pull the visuals according to the needs of students with hearing impairment. Monopoly Hijaiyah is a media learning which was able to help students with hearing impairment to introduce terms of show, mention and wrote hijaiyah letters. Design research used one group design pretest-posttest. The data collected based on the results pretest and posttest processed using the Wilcoxon test. Based on the results of the testing hypotheses, so obtained Tcount=12 and based on the critical to Wilcoxon test on the level of signification in 0,05 the amount N consisting of three students, so obtained t-table = 0, Ho rejected. Thus hypotheses from the research are accepted. The research obtained the conclusion that is in the use of Monopoly Hijaiyah improves knowledge hijaiyah letters in students with hearing impairments. Therefore it is suggested that media be considered for teachers to implement in learning in the class.